2016
DOI: 10.1080/14764172.2016.1202421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neodymium–yttrium–aluminum garnet (Nd:YAG) pulsed high-intensity laser therapy on full thickness wound healing in an experimental animal model

Abstract: Nd:YAG HILT stimulated fibroblast proliferation and increased extracellular matrix production. We expect that this therapy could accelerate the wound-healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…28 The physiological effects of laser therapy include alterations in cell membrane permeability, with changes in intracellular calcium levels; increased cellular metabolism; altered DNA and RNA synthesis; fibroblast proliferation; activation of T lymphocytes, macrophages and mast cells; increased synthesis of endorphins and decreased synthesis of bradykinin. 29 Hong et al 25 reported the biostimulatory effects of HILT on wound-healing process, demonstrating that HILT could promote fibroblast proliferation and result in significant increases in collagen synthesis, granulation tissue formation and extracellular matrix production. Furthermore, the anti-inflammatory effect of HILT can be achieved by the modulation of the inflammatory response, exudation, alteration and proliferation; stimulation of the readaptive reactions of the organism and inhibition of cyclooxygenases and lipoxygenases with modulation of prostaglandin and prostacyclin synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The physiological effects of laser therapy include alterations in cell membrane permeability, with changes in intracellular calcium levels; increased cellular metabolism; altered DNA and RNA synthesis; fibroblast proliferation; activation of T lymphocytes, macrophages and mast cells; increased synthesis of endorphins and decreased synthesis of bradykinin. 29 Hong et al 25 reported the biostimulatory effects of HILT on wound-healing process, demonstrating that HILT could promote fibroblast proliferation and result in significant increases in collagen synthesis, granulation tissue formation and extracellular matrix production. Furthermore, the anti-inflammatory effect of HILT can be achieved by the modulation of the inflammatory response, exudation, alteration and proliferation; stimulation of the readaptive reactions of the organism and inhibition of cyclooxygenases and lipoxygenases with modulation of prostaglandin and prostacyclin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Using a laser with a wavelength of 1064 nm provides the best absorption and penetration into tissue as its absorption by tissue chromophores, such as haemoglobin, melanin and water, is lower,; thereby enhancing the wound-healing process. 25 The 1064 nm laser wavelength has other beneficial properties. It provides photobiomodulation by inducing increases in oxygen consumption, endogenous ATP synthesis and fission rate rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…It is well worth noting that the main mechanism by which the Q-switched Nd:YAG laser exerts its action on tissues is the photo-mechanical effect, while that exert by the long-pulsed Nd:YAG laser is the photo-thermal effect [ 7 , 8 ]. The neodymium-doped yttrium aluminum garnet (Nd:YAG laser) is a laser that issues various wavelengths and can operate in continuous, long-pulsed, Q-switched, or potassium titanyl phosphate (KTP) modes.…”
Section: Introductionmentioning
confidence: 99%
“…Q-switched Nd:YAG laser 1064 nm is able to penetrate the tissue more deeply and reduce tissue damage. Thanks to its shorter pulse width, Q-switched Nd:YAG laser delivers, selectively in the upper dermis, higher doses of energy and stimulates cellular metabolism, with lower temperature and thus damages for epidermidis [ 7 , 8 ]. A number of laser devices and light sources, emitting at various wavelengths through non-ablative mechanisms, have been described that effectively improve the appearance of aged skin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation